PEMBANGUNAN SUMBER DAYA MANUSIA PADA SEKOLAH KEJURUAN DI INDONESIA: TANTANGAN DAN PELUANG DI ERA REVOLUSI INDUSTRI 4.0 - Ridwan, Mahmud (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2021)
Vocational education is one of education that is unique in the orientation of creating work-ready people with the appropriate knowledge and skills. World changes in the era of the industrial revolution 4.0, provide new direction in enhancing human resource in the form of new challenges. This research was conducted to see the challenges and opportunities that exist in the industrial era 4.0 related to the development of human resource in vocational education in Indonesia. The study in this research used the literature method. Literature study is used to see the literature related to the subject. From this topic, conclusion were drawn, so that it can be seen some of the challenges that exist in Industry 4.0. but behind that, there are also opportunities that vocational education has that can be maximally utilized in building quality human resource.